The perception of journalists on climate change: an initial study in the newspaper Gazeta do Povo - Beling Loose, Eloisa (2016)
This text seeks to determine how journalists of the largest Paraná (southern Brazil) newspaper, Gazeta do Povo, perceive, within its daily production routines, the subject of climate change and its possible risks. This paper aims to verify how the news production on the issue is understood by journalists responsible for writing or editing news on climate change in the context of a regional/local newspaper. Among the findings, it was observed that there is an understanding, by journalists, about the relevance of media approach to the subject, although the logic of coverage routines and the complexity of the issue do not allow further deepening, especially in relation to risks inherent in the environmental phenomenon.